Successful Replantation of Avulsed Teeth with Arch Bar Fixation and Extraoral Root Canal Treatment: A Case Report - Hardini, Nadia; Setyawan, Aris; Chairani, Elissa; Dhaifullah, Jihan Nabilatsanya; Azis, Anis Hilda Intani; Sulistyono, Farah Divanti; Nuraini, Luthfi (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: Tooth avulsion is the detachment of a tooth from its socket due to mechanical trauma. It was reported that a 26-year-old male patient was referred from the RSND Emergency Department to the dental clinic with complaints of loose front teeth of the upper jaw due to a traffic accident. From the intraoral examination, tooth 11 was partially detached from its socket, tooth 12 had an Ellis class II fracture, and a torn wound on the labial mucosa of the lower lip. Treatment of choice in this case is replantation and fixation of avulsed teeth, which aim to restore the physiological function of the teeth.Method: Treatments include extraoral root canal treatment and replantation and fixation of the arch bar. Result: Clinical and radiographic examinations during post-treatment control showed periodontal tissue healing and bone formation.Conclusion: It was concluded that the success rate of tooth replantation, in this case, was good, and using the right arch bar provided stability to the avulsed tooth, thereby accelerating the healing of the periodontal ligament